Day–night contrast as source of health for the human circadian system. (April 2014) - Martinez-Nicolas, Antonio; Madrid, Juan Antonio; Rol, Maria Angeles
<x xml:space="preserve">Abstract</x> Modern societies are characterized by a 24/7 lifestyle (LS) with no environmental differences between day and night, resulting in weak zeitgebers (weak day light, absence of darkness during night, constant environmental temperature, sedentary LS and frequent snacking), and as a consequence, in an impaired circadian system (CS) through a process known as chronodisruption. Both weak zeitgebers and CS impairment are related to human pathologies (certain cancers, metabolic syndrome and affective and cognitive disorders), but little is known about how to chronoenhance the CS. The aim of this work is to propose practical strategies for chronoenhancement, based on accentuating the day/night contrast. For this, 131 young subjects were recruited, and their wrist temperature (WT), activity, body position, light exposure, environmental temperature and sleep were recorded under free-living conditions for 1 week. Subjects with high contrast (HC) and low contrast (LC) for each variable were selected to analyze the HC effect in activity, body position, environmental temperature, light exposure and sleep would have on WT. We found that HC showed better rhythms than LC for every variable except sleep. Subjects with HC and LC for WT also demonstrated differences in LS, where HC subjects had a slightly advanced night phase onset and a general increase in day/night contrast. In addition, theoretical high day/night contrast calculated using mathematical models suggests an improvement by means of LS contrast. Finally, some individuals classified as belonging to the HC group in terms of WT when they are exposed to the LS characteristic of the LC group, while others exhibit WT arrhythmicity despite their good LS habits, revealing two different WT components: an exogenous component modified by LS and another endogenous component that is refractory to it. Therefore, intensifying day/night contrast in subject's LS has proven to be a feasible measure to chronoenhance the CS.